EKSPERIMENTASI MODEL PEMBELAJARAN REASONING AND PROBLEM SOLVING DITUNJANG MEDIA POWER POINT TERHADAP HASIL BELAJAR MATERI LINGKARAN - Widyaningrum, Amalia Zulvia (JURNAL E-DUMATH, 2016)
The purpose of this study is to determine the differences between theresults of the students learning achievement using reasoning and problemsolving models supported by power point media and direct instructionmodels. The population was all of the students in second grade of SMP N1 Satu Atap 2 Negerikaton in the academic year 2015-2016, the samplingtechnique used cluster random sampling. Learning achievement data wasgotten from the test used essay consists of 5 items then it were analyzed byusing t-test. The results of this study showed there are differences in thestudentâs learning achievement average between these two models and thestudentâs learning achievement average using reasoning and problemsolving models supported by power point media is better than using directinstruction models.Keywords: reasoning and problem solving models, power point media, directinstruction model